Development of Students’ Worksheet Through Guided Inquiry Model to Increase Science Process Skills in The Harmonic Vibration Subject - Puspa Imroah Ramadhani; Eko Hariyono; Elok Sudibyo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study uses guided inquiry models to test the relationship between the Student Worksheets and Science process skills on the Harmonic Vibration subject. Method: This research uses an experimental method with subjects on high school students in two State Islamic School 1 Sumenep classes. Result: Through comprehensive equipment and questions. This research results in several aspects as follows: (1) the average validity on the Student Worksheet (SW) is 3.58, which is categorized as a very-valid; (2) the exciting aspect of SW is 93% with attractive criteria, the understanding SW is 87% with easy-to-understand criteria, clarity in terms of font size and typeface is 100% with clear criteria, clarity in terms of language aspects is 92% with clear criteria, as well as clarity of description supported by graphic illustrations of 87% with clear criteria; (3) The effectiveness of SW is measured through the pre-test and post-test which depicts that there is an increase in students' science process skills after the using learning tools and guided inquiry learning models. Novelty: This research contributes to the development of indicators in student's worksheets relating to science process skills, including formulating a problem, making a hypothesis, determining the experimental variable, defining operational definitions of variable, creating a data table, creating a finding and analysis, and making a conclusion.